Nonlinear equations with degenerate operator at fractional Caputo derivative - Plekhanova, Marina V. (Mathematical methods in the applied sciences, 2017)
At first, the existence of a unique solution for the Cauchy problem to nondegenerate fractional differential equation was proved. These results were used for research of the unique solvability for the initial Cauchy and Showalter–Sidorov problems to differential equations in Banach spaces with degenerate operator at fractional Caputo derivative in linear and nonlinear cases. results are applied to the research of an initial boundary value problem for time‐fractional order Oskolkov system of equations. Copyright © 2016 John Wiley & Sons, Ltd.